Effectiveness of individual‐focused interventions to prevent chronic disease. (September 2014) - Saeed, Sara; Golfam, Mohammad; Beall, Reed F.; Ashbury, Fredrick D.; Palmer, Lyle J.; Little, Julian
Abstract Background The burden of chronic disease is projected to assume crisis proportions in most parts of the world by the middle of the century, focusing attention on the need for preventive interventions. We identify and review published research on primary prevention individual‐level interventions in current practice and describe and discuss the limitations of the current evidence. The report facilitates prioritizing a research agenda for potential interventions that might be investigated within cohort studies. Materials and methods This study is a rapid review. Computerized database searches (PubMed and EMBASE) were performed in October 2012 to identify articles on primary prevention interventions that are directed at the individual level. Potentially, relevant International Agency of Research on Cancer handbooks and monographs were also reviewed. The review includes articles reported in English on the efficacy or effectiveness of a preventive intervention in an adult population. It excludes articles on alcohol or tobacco smoking. Results Many chronic disease interventions directed at individuals report a protective effect in the short term and some evidence for the efficacy of chemoprevention in chronic disease prevention exists. Evidence these effects persist in the longer term is inconsistent. Conclusions There are currently only limited evidence‐based preventions for most chronic diseases, for which a summary is available in Table A1 (see Appendix B). Most individual‐level intervention research studies have been conducted using case–control designs and some small, randomized studies. There are fewer impediments to lifestyle modifications when compared to prevention using chemoprevention and vaccination or other methods of prevention of persistent infection.